Faktor yang Berhubungan dengan Perilaku Minum Obat Terapi Pencegahan Tuberkulosis (TPT) di Wilayah Kerja Puskesmas Putri Ayu Kota Jambi - Aditya Gumara; Rumita Ena Sari; Rizalia Wardiah; Guspianto Guspianto; Helmi Suryani Nasution (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Globally, tuberculosis has affected 10 million people in world. 1,060,000 of these cases are from Indonesia. Providing Tuberculosis Preventive Therapy (TPT) is one of the strategies TB control. TPT achievements in Jambi City are low (1.65%) 2022 and (1.08%) 2023. Putri Ayu Health Center is health center with most TB cases in Jambi City with total 84 cases 2022 and 95 cases 2023. This study aims to determine factors associated with behavior of taking medication for TPT in working area of Putri Ayu health center. Research method used was quantitative with cross-sectional design. Population in this study people who were at home with TB patients who sought treatment at Putri Ayu health center with sample size of 78 people, sample selection technique used purposive sampling. Results of study, there was a significant relationship in perceived vulnerability with p-value = 0.001, perceived severity with p-value = 0.000, perceived benefits with p-value = 0.000, perceived barriers with p-value = 0.000, and perceived self-efficacy with p-value = 0.009 to behavior of taking TPT drugs. It’s hoped there will be an increase in role of health workers in providing complete counseling and education related to TPT drugs to the community.